A psychobiography of Helen Martins - Mitchell, Donna Leigh (Rhodes University, Faculty of Humanities, Department of Psychology, 2014)
Helen Martins devoted approximately the last thirty years of her life to converting her family home into a unique fantasy world which she named the Owl House. Since her death in 1976 the Owl House has become a national monument and museum in South Africa. Throughout her life Helen was considered by most of the surrounding villagers to have been strange, and she withdrew increasingly from society. However, she appeared to have contained a desire for human connection. There are several instances in which she expressed this desire, such as through the numerous letters which she wrote to fellow artists. The existing body of literature on Helen illustrates the complex nature of her personality; however the question of which personality style she best typifies has remained unanswered. In order to answer this question a psychobiography was conducted on Helen. Psychobiographies entail a biographical representation of a person's life history to which a psychological theory is applied. The psychological theory utilised within the current study was Millon's (1969/1996) Biosocial- Learning Theory. Thus, the chief objective of this study was to describe and interpret Helen's personality style through the use of Millon's (1969/1996) Biosocial-Learning Theory. Alexander's model of data extraction and Miles and Huberman's three step approach were implemented in order to reduce, organise and analyse the data. The findings of this study reflected that Helen deteriorated from one of Millon's (1969/1996) proposed personality styles to another as she aged. The current findings may illuminate Helen's motives for obsessively devoting her life to the creation of her fantasy world.
Keywords: Martins, Helen Elizabeth, 1897-1976 -- Criticism and interpretation; Psychology -- Biographical methods; Women sculptors -- Psychology; Psychohistory; Personality -- Social aspects; Personality -- Age factors; Personality assessment; Personality change